Modulation of NK Cell Function by Genetically Coupled C-Type Lectin-Like Receptor/Ligand Pairs Encoded in the Human Natural Killer Gene Complex - Bartel, Yvonne; Bauer, Björn; Steinle, Alexander (Frontiers in Immunology, 2013)
Functional responses of Natural Killer (NK) cells including eradication of ‘harmful’ cells and modulation of immune responses are regulated by a broad variety of activating and inhibitory NK receptors. Whereas the leukocyte receptor complex (LRC) encodes for NK receptors of the immunoglobulin superfamily, genes of C-type lectin-like NK receptors are clustered in the mammalian Natural Killer Gene Complex (NKC). Besides the thoroughly studied C-type lectin-like receptors (CTLR) NKG2D, CD94/NKG2x and members of the murine Ly49 subfamily, the NKC also encodes for NK receptors of the less characterized NKRP1 subfamily. The prototypic mouse NKRP1 receptor is Nkrp1c (also known as NK1.1), while human members of the NKRP1 subfamily are NKRP1A, NKp80 and NKp65. The latter are not straight homologues of mouse NKRP1 receptors, but share distinct subfamily-specific traits classifying them as members of the NKRP1 subfamily. Ligands of the human NKPR1 receptors are likewise C-type lectin-like glycoproteins belonging to the CLEC2 subfamily (i.e. LLT1, AICL, and KACL), and are encoded in the NKC in tight genetic linkage to their respective receptors. Similarly, certain members of the mouse NKRP1 subfamily interact with genetically coupled CLEC2 glycoproteins, while the reasons for this intriguing tight genetic linkage remain unknown. Recent studies provided new and unique insights into the expression, interaction, and signaling of NKRP1 receptors and their ligands, thereby substantially advancing our understanding of their function and biology. Here, we review our current knowledge on NKRP1 receptors and their genetically linked CLEC2 ligands with an emphasis on the human receptor/ligand pairs NKRP1A-LLT1, NKp80-AICL, and NKp65-KACL.